Miscanthus x giganteus culture on soils highly contaminated by metals: Modelling leaf decomposition impact on metal mobility and bioavailability in the soil-plant system - Al Souki, Karim Suhail; Liné, Clarisse; Louvel, Brice; Waterlot, Christophe; Douay, Francis; Pourrut, Bertrand (Ecotoxicology and environmental safety, 2020)
Miscanthus x giganteus is suggested as a good candidate for phytostabilization of metal-polluted soils. Its late harvest in winter generates large amounts of leaf litter on the soil surface. However, little is known about the mobility and the bioavailability of metals following leaf decomposition and the consequences on the succeeding culture. Ex situ artificial aging for 1, 3, and 6 months was conducted with miscanthus leaf fragments incorporated into three agricultural soils displaying a gradient concentration in Cd (0.6, 3.1 and 7.9 mg kg-1), Pb (32.0, 194.6 and 468.6 mg kg-1), and Zn (48.4, 276.3 and 490.2 mg kg-1) to simulate the leaf litter input over 20 years of miscanthus culture. We investigated the impacts on physicochemical and biological soil parameters, CaCl2-extractable metal, and their subsequent ryegrass shoot concentrations, and hence on ryegrass health. The results showed that the amended soils possessed higher pH along with greater available phosphorous and soil organic carbon values. The respiratory activity and microbial biomass carbon in the amended soils increased mainly after 1 month of aging, and decreased afterwards. Despite the higher Pb- and Zn-CaCl2 extractability in the amended soils, the phytoavailability slightly increased only in the most contaminated soils. Moreover, leaf incorporation did not affect the ryegrass biomass, photosynthetic pigment contents, nor the antioxidative enzyme activities. Conclusively, leaf incorporation induced slight variations in soil physicochemical and biological parameters, as well as metal extractability, but not to an extent that might cause a considerable threat to the subsequent culture. Nevertheless, these results are preliminary data that require confirmation by long-term in-situ experimentations as they reflect the modelization of long-term impact of leaf decomposition on soil-plant system.
Keywords: Ryegrass; Metals, Heavy; Lolium; látky znečišťující půdu; Metal cycle; biologická dostupnost; Biodegradation, Environmental; biodegradace; Plant Leaves; Miscanthus; Organic matter restitution; teoretické modely; Plant Roots; Poaceae; Models, Theoretical; Ex-situ experiment; těžké kovy; kořeny rostlin; Soil Pollutants; biomasa; Soil; Stress biomarkers; jílek; lipnicovité; Biomass; Metal behavior; listy rostlin; půda; Biological Availability